ANALISIS PENGARUH BUDAYA ORGANISASI, KEPUASAN KERJA, DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA KARYAWAN (Studi pada Karyawan Kantor PT. Telekomunikasi Indonesia Tbk. Divisi Regional IV Jawa Tengah dan Daerah Istimewa Yogyakarta) - Prawira, Samuel Jaka; Darmastuti, Ismi (Diponegoro Journal of Management, 2015)
The  key  of  organization’s    success    is  generated  by  each  of the  resources  of  the organization. It can be said that human resources is one of the determining factors for winning the business competition in a short period and long term. The human factor is not only the holders of an important role for the organization, but also a vital tool for organizations because it can not be replaced completely by other resources. The business competition today is requiring the role of human resources to have a competitive advantage and an organization should be able to improve the employee’s performance.This  research  aims  to  analyze  the  effect  of  variables  of organizational  culture,  job satisfaction  and  organizational commitment  on  employee  performance.  This  research  was conducted at PT Telkom Indonesia, Tbk Regional IV Jateng- DIY. The number of samples specified by set as much as 76 respondents using Convenience sampling methods and Methods data analysis used was multiple linear regression analysis using SPSS.The results of testing againts the hypothesis, indicating that organizational culture variable has positive influence on employee’s performance. Job satisfaction variable has positive influence on the employee’s performance, and  organizational commitment variable has positive influence on employee’s performance.